Analisis Penilaian Tingkat Kesehatan Bank dengan Menggunakan Metode CAMEL - Jeveline Latumahina (JMK (Jurnal Manajemen dan Kewirausahaan), 2018)
This study aims to determine the health condition of PT. BPR Bintang Tulungagung by using CAMEL method (Capital, Assets Quality, Management, Earnings, Liquidity) during the period 2012-2016. The subject of this research is PT. BPR Bintang Tulungagung . While the object in this study is the financial reports of PT. BPR Bintang Tulungagung within period 2012-2016. Data analysis method used is CAMEL method. The results showed that the health level of PT. BPR Bintang Tulungagung within the period 2012-2016 all received a healthy predicate because the value of CAMEL credit obtained is above 81 (healthy minimum limit) in 2012 of 96,67, the year 2013 is 96,92, the year 2014 of 96,92, the year 2015 at 95,50 and in 2016 at 97,08.